PENYUSUNAN MODEL MANAJEMEN PENGELOLAAN KEUANGAN DESA PASCA PEMBERLAKUAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 (Kajian Pada Desa Liliboi Kecamatan Leihitu Kabupaten Maluku Tengah dan Desa Rutong Kecamatan Leitimur Selatan Kota Ambon) - Stenly Salenussa (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2019)
With the preparation of the village financial management model according to the Undang-Undang No. 2 of 2014 and the Peraturan Menteri Dalam Negeri Nomor 113 Tahun 2014, it will facilitate the village government in managing the Village Fund Budget which is given specifically to Liliboi village, West Leihitu District, Central Maluku Regency and Rutong village, South Leitimur District Ambon City. The village medium term development plan, which was initiated through the village Musrembang forum up to the principles of transparent, accountable, participatory financial management, and carried out in an orderly discipline and the budget is the basis for implementation of village financial management. The results achieved were the absorption of village funds for the field of community empowerment, enjoyed by the people of both villages. To achieve the target, the study was designed with a qualitative approach, i.e. the data collected was not in the form of figures, but rather came from interviews, questionnaires, and other official documents. The research design in this study is descriptive research.